Globalization as an Affront to Indigenous Cultural World Views: Implications for Africa - Ihejirika, Cardinal; Asike, Jude (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2018)
Globalization espouses the idea of universalization of cultures and economies toward intensified social relations which unite distant localities. Its project cuts across geographical boundaries, cultures and sovereignties with the presumed aims of socio-political and economic development and unity of nations. However, it proposes monolithic kind of unity, which blurs cultural lines, destroys the beauty of cultural diversity, stifles social control, and diminishes cultural identities and distinctions thereby leading to forced acculturation. Besides creating a moral lacuna by its introduction of foreign ideologies into indigenous societies, globalization (or more particularly, cultural globalization) seems to have left Africans confused and without a defined ideology of life and development. Consequently, the worrisome impression created is that globalization is at best, Eurocentric agenda. Informed by these inequalities as witnessed by indigenous societies, this paper, which limitedly focuses on the harm of globalization on indigenous cultures (using the African-Igbo as a case study) suggests an adjusted relativist global culture to be called the cultural pluralism approach. This consciousness-raising process is advanced to check the pitfalls of a context-free global culture, which destroys indigenous cultures. The analytical method is adopted for this research.